Increased Aerosol Extinction Efficiency Hinders Visibility Improvement in Eastern China. Issue 20 (16th October 2020) - Liu, Jingyi; Ren, Chuanhua; Huang, Xin; Nie, Wei; Wang, Jiaping; Sun, Peng; Chi, Xuguang; Ding, Aijun
Abstract: Though China has witnessed substantial particular matter pollution mitigation owing to the strict emission control in recent years, the frequency of haze events with low visibility is not improved as much as expected, especially in cold seasons. Here, 6‐year wintertime observations, satellite retrievals, a thermodynamic model, and theoretical calculation were integrated to better understand the complex influence of aerosol chemical composition and hygroscopic behaviors on visibility impairment. We found that the proportion of nitrate in aerosol mass concentration increased by approximately 10% from 2013 to 2018. Such a transition in aerosol chemical compositions together with increasing ambient humidity in past years jointly enhanced aerosol extinction efficiency, and the elevated proportion of nitrate played an increasingly critical role after 2017. The increased aerosol extinction efficiency is responsible for the less improved visibility despite large decrease in aerosol mass concentrations in eastern China. Plain Language Summary: Atmospheric aerosol degrades regional visibility as a result of light extinction, which is highly linked with aerosol chemical composition and particle size growth in humid environment. Due to a much sharper drop of sulfur emission than nitrogen emission in China, aerosol has become increasingly nitrate‐dominant. The transition in aerosol chemical compositions together with increasing ambient humidity in past years may jointly alter aerosol hygroscopic behaviors and enhance aerosol extinction efficiency. In consequence, although substantial mitigation of aerosol pollution has been achieved in recent years, hazy days with low visibility still frequently occur in eastern China. Key Points: Visibility improvement is not obvious in eastern China despite strict emission control Nitrate proportion in PM2.5 has substantially increased due to unbalanced precursor emission control Increased nitrate proportion and humidity enhance aerosol hygroscopicity and extinction efficiency